Product Quality Improvement through Effective Operational Management - Hasyim, Hasyim; Bakri, Muhammad (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study explores the impact of advanced technologies and strategies on supply chain optimization within operational management, aiming to understand how AI, ML, IoT, blockchain, effective inventory management, supplier relationship management, risk management strategies, and sustainability practices enhance supply chain performance. Research Design and Methodology: The study uses a qualitative research design, including semi-structured interviews with supply chain experts from various industries and document analysis. The thematic analysis identifies patterns and themes, offering a detailed understanding of factors contributing to supply chain optimization. Findings and Discussion: The study reveals advanced technologies significantly improve demand forecasting accuracy, real-time decision-making, and supply chain transparency. Strategies such as JIT, Lean Inventory, EOQ, and VMI optimize inventory levels and reduce costs. Strong supplier relationships and robust risk management strategies enhance supply chain resilience and agility, while sustainability practices lead to cost savings, improved brand reputation, and regulatory compliance. The findings support the hypothesis that technological integration and strategic management enhance supply chain performance, aligning with the resource-based view and dynamic capabilities theories. Implications: This research provides insights for businesses seeking to optimize their supply chains. It highlighting the need for a holistic approach integrating technological solutions with human and organizational factors. The findings offer practical guidance for implementing advanced technologies and strategies, contributing to scientific understanding and practical applications in supply chain management.